2020
DOI: 10.3390/ijms21238940
|View full text |Cite
|
Sign up to set email alerts
|

Rice Bran and Vitamin B6 Suppress Pathological Neovascularization in a Murine Model of Age-Related Macular Degeneration as Novel HIF Inhibitors

Abstract: Pathological neovascularization in the eye is a leading cause of blindness in all age groups from retinopathy of prematurity (ROP) in children to age-related macular degeneration (AMD) in the elderly. Inhibiting neovascularization via antivascular endothelial growth factor (VEGF) drugs has been used for the effective treatment. However, anti-VEGF therapies may cause development of chorioretinal atrophy as they affect a physiological amount of VEGF essential for retinal homeostasis. Furthermore, anti-VEGF thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 51 publications
1
33
0
Order By: Relevance
“…Extraction of total retinal protein and electrophoresis followed by visualization of target bands were conducted as same as described in our previous papers [ 19 , 35 , 36 , 68 , 69 ]. Primary antibodies that we used in this study are anti-HIF-1α (1:500, Cat #36169, Cell Signaling Technology, Danvers, MA, USA), anti-synaptophysin (1:1000, Cat #SAB4502906, Sigma, Tokyo, Japan), and anti-β-Actin (1:5000, #3700, Cell Signaling Technology, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Extraction of total retinal protein and electrophoresis followed by visualization of target bands were conducted as same as described in our previous papers [ 19 , 35 , 36 , 68 , 69 ]. Primary antibodies that we used in this study are anti-HIF-1α (1:500, Cat #36169, Cell Signaling Technology, Danvers, MA, USA), anti-synaptophysin (1:1000, Cat #SAB4502906, Sigma, Tokyo, Japan), and anti-β-Actin (1:5000, #3700, Cell Signaling Technology, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Both the mRNA and protein levels of C1QBP increased under hypoxic conditions and decreased upon treatment with the HIF-1α inhibitor as expected ( Figure 1E ). Accordingly, we further detected the protein level of vascular endothelial growth factor (VEGF), von Hippel-Lindau tumor suppressor (VHL), E-cadherin 1 (E-cad), and β-tubulin, that are reported to be regulated by hypoxia and/or HIF-1α ( Bordji et al, 2014 ; Ning et al, 2018 ; Ibuki et al, 2020 ; Urrutia et al, 2020 ; Yang et al, 2020 ) ( Supplementary Figure 2B ). Based on the data from the JASPAR database, we generated several primers for HIF-1α containing multiple binding sites on the C1QBP promoter ( Figure 1F ).…”
Section: Resultsmentioning
confidence: 99%
“…Ibuki et al, discovered several HIF inhibitors through extensive screenings of food ingredients, and found that a diet containing these ingredients was effective in reducing the risk of laser-induced CNV in mice [ 38 , 39 , 40 ]. Furthermore, treatment of these ingredients/compounds reduced V egf mRNA expression as well as HIF activation under CoCl 2 -induced pseudo hypoxic conditions [ 38 , 39 , 40 ].…”
Section: Potential For Hif Inhibitorsmentioning
confidence: 99%
“…Ibuki et al, discovered several HIF inhibitors through extensive screenings of food ingredients, and found that a diet containing these ingredients was effective in reducing the risk of laser-induced CNV in mice [ 38 , 39 , 40 ]. Furthermore, treatment of these ingredients/compounds reduced V egf mRNA expression as well as HIF activation under CoCl 2 -induced pseudo hypoxic conditions [ 38 , 39 , 40 ]. Otherwise, Lee et al found that resveratrol significantly reduced the expression of HIF-1α and VEGF-A in human ARPE19 cells and CNV mouse models by inhibiting the PI3K/AKT/mTOR signaling pathway, which promotes proteasome-mediated degradation of HIF-1α.…”
Section: Potential For Hif Inhibitorsmentioning
confidence: 99%